MODEL KEPEMIMPINAN KEPALA DESA DALAM MEWUJUDKAN PEMBANGUNAN DESA WISATA: (Studi Tentang Model Kepemimpinan Kepala Desa Peniwen Kecamatan Kromengan Kabupaten Malang) - Wiyono, Hadi; Soeltanto, Taufiq; Jain Wijayanti, Alviolenta (STIA MALANG, 2024)
Leadership style is a method used in the leadership process that is implemented in a person's leadership behavior to influence others, to act according to what he wants. This study aims to determine the leadership style of the Peniwen village head in realizing the development of a tourist village using qualitative research type phenomology. The results showed that the leadership style of the Peniwen village head was included in the charismatic leadership style when juxtaposed with the theory of Robert, Albanese, David D, Van Fleet (1994) and the Peniwen Village Head had implemented it in his leadership and proved that with the charismatic style the Peniwen village head succeeded in realizing the development of a tourist village through the preparation of programs.